An Analysis of Efficiency of General Insurance Industry in India - Sinha, Abhijit; Bandopadhyay, Kalpataru (Universiti Utara Malaysia Press, 2016)
It is well known that the overall insurance sector in India has been undergoing a series of reforms from time to time. The drastic change that re-designed the contours of the industry is the implementation of the Malhotra Committee Recommendations which opened up the landscape to the private non-life insurers in 2000. The present study has been taken up to determine the efficiency of the non-life sector and the insurers using Data Envelopment Analysis (DEA). The empirical research also aims to statistically test whether there is any year-wise significant difference between the two sectors in respect of the overall efficiency. For the purpose, appropriate statistical test is applied. The study is based on secondary data collected from the Insurance Regulatory Authority of India (IRDA) Annual Reports. The sample size for this study is twelve including all the four insurers from the public sector and the remaining from the private sector. The results of the analysis showed that in terms of technical and pure technical efficiency, the overall result of the public sector surpasses that of the private. However, the findings of the Mann-Whitney U Test revealed that the result with respect to the statistical difference is mixed.